DIALEKTIKA RELASIONAL PASANGAN ANTAR NEGARA: STUDI KASUS PADA PASANGAN BELGIA - INDONESIA - Teguh, Monika; Swastika, Gabriela Laras Dewi; Gozali, Citta Catherine (LPPM Stikosa - AWS, 2025)
A relationship cannot be limited by territorial or cultural boundaries. However, it must be recognised that the challenges in establishing intercultural relationships are also great, especially in phenomena such as COVID-19. The initial tension in relational dialectics is mostly triggered by changes in situations that become